Analysis of AtCLV3 promoter and its utilization for expressing cre recombinase in Indian mustard - DHATWALIA, DEEPA; MAITHREYI, R SHUBHRA; BHATT, DEEPA; PANDE, VEENA; BHATTACHARYA, RAMCHARAN (The Indian Journal of Agricultural Sciences, 2021)
Constitutive expression of the transgene is not always desirable because of its pleiotropic effects and metabolic pay-off. Therefore, tissue-specific expression of the transgene can be more significant in reducing the unintended effects of the transgene. The strength as well as tissue and temporal specificity of the promoter activity is dependent on cis-acting elements and transcriptional factors. The objective of this study was to analyse the promoter elements in Arabidopsis CLV3 promoter and its utilization in driving tissue specific expression of the cre recombinase gene in Indian mustard. The study was carried out at ICAR-NIPB, New Delhi, during 2015-19. In this study, in silico analysis of Upstream Regulatory Modules (URMs) of CLV3 gene led to the identification of several sequence motifs related to its meristematic tissue specific expression. Further, the CLV3 promoter was used for driving the expression of a cre recombinase gene in transgenic lines of B. juncea plants for functional analysis. The Cre-transgenic lines are useful for Cre/lox mediated marker gene excision in transgenic B. juncea.